Sexual Selection and the Brotherhood of Humans: Does the argument of The Descent of Man confirm The sacred cause thesis? - Ginnobili, Santiago (2023)
Desmond and Moore point out that the key to understanding Darwin’s The Descent of Man is his abolitionist motivation and his advocacy that races constitute subspecies. Roberta Millstein raises some doubts about the importance of this motivation. She points out that the inclusion of the extensive section devoted to non-human animals is not justified by Darwin’s treatment of humans per se, because his explanation of the origin of races is peculiar. In this sense, she argues that Darwin’s specific explanation of the origin of races does not confirm the central importance that Desmond and Moore give to Darwin’s abolitionism. In this paper I have two different aims. On the one hand, to show that the human case actually is based on the treatment of nonhuman animals, and consequently, Darwin’s argument is not as poor as Millstein believes. My second goal, taking Millstein’s challenge seriously, is to show that Darwin’s explanation of the origin of races does confirm the Desmond and Moore thesis in a deeper sense than the one they propose themselves. For the anti-slavery motivation could not only explain the fact that Darwin sees all humans as forming the same species, but the specific explanation he gives for the origin of races.